The Effect of Credit Portfolio Concentration on the Risk and Profitability During the Covid-19 Pandemic Evidence From Commercial Banks in Indonesia - Argado Insani HUTABARAT; Eko RIZKIANTO (Communications of International Proceedings, 2022)
This paper examines the effect of credit portfolio concentration on bank performance during the COVID-19 Pandemic, which is important because banks must adopt the right policies to avoid the risk of payment default caused by economic shock during the COVID-19 Pandemic. The nature of this research is quantitative, using the EGLS Panel estimation method on panel data from 47 commercial banks that went public in Indonesia during 2016–2021. In the present study, the Hirschman-Herfindahl Index (HHI) based on the economic sector is used as a measure of the concentration credit portfolio, non-performing loans (NPL) as a measure of risk, and return on equity (ROE) as a measure of profitability. This research reveals that the concentration of the credit portfolio will reduce credit risk before the COVID-19 pandemic. On the contrary, after the COVID-19 pandemic, the concentration of credit portfolios will increase credit risk. On the other hand, credit portfolio concentration will make banks less profitable before the COVID-19 pandemic and more profitable after the COVID-19 pandemic.
Keywords: Banking; Diversification; Npl; Roe